Potensi sumber tenaga di semenanjung Semporna, Sabah - Sanudin Hj. Tahir; Felix Tongkul; Harry Benedick (Universiti Malaysia Sabah, 2003)
Geological studies of the Silimpopon syncline. southeastern part of Sabah, offer an opportunity to exploit the potential of the coal rich sequence of the area. On the basis of the characteristics of the sedimentary sequences and their stratigraphic position, a model is proposed to explain the sequential trends, taking into account the importance of sedimentology and sedimentary environments associated with lateral and vertical changes according to the distribution pattern.